Influence of Customer Engagement on E-WOM and Repurchase Intention Through Customer Equity of Masculine Cosmetic Products (Study on Tokopedia & Shopee Users) - Aditya Pramana; Agus Hermawan; Wening Patmi Rahayu (Transpublika Publisher, 2024)
This paper purposes to obtain evidence of whether there is a direct or indirect influence between customer engagement, Customer equity, e-WOM, and Repurchase intention on m-commerce customers (Tokopedia and Shopee) in Indonesia. This paper applies a quantitative research approach with explanatory research methods and in-depth descriptive analysis. This study uses infinite population for the population used, because the number of users of the Tokopedia or Shopee m-commerce applications in Indonesia is not accurately recorded, with predetermined criteria. The nonprobability sampling method chosen by the author in this paper as a sampling technique used using purposive sampling technique, because the unlimited population size, then 5% margin of error, with 95% confidence level, and 50% population proposition resulted from the calculation is as many as 385 samples of m-commerce users who have purchased masculine cosmetics as sample respondents. The data analysis technique uses an associative, quantitative and SEM-PLS approach. For novelty or novelty in this research, researchers have scientific suspicions on two other drivers of customer equity, namely; Value Equity, and Relationship Equity can directly influence the occurrence of e-WOM and use m-commerce user respondents who have purchased masculine cosmetic products. Results of the study showed that all variables have a positive influence on each other, either directly or indirectly and significantly, except for the customer engagement variable on repurchase intention which showed no significance. The impact of the study could be a reference for m-commerce in increasing users and directing them to constructive goals.